Estructuración del mecanismo para la aplicación de la gestión por procesos en la cadena de panaderías Relámpago - Loachamín Melo, Evelyn Jadira (2015)
The thesis proposal allows knowing improvement alternatives, both in society and in companies, it should be noted that we are now facing a globalized world requires us what excellence and competitiveness in each of the activities developed, hence the idea of this plan emerges for the proper conduct of the empresa.El approach to drive in this project is to identify the processes and systems management developed in the company and in particular the interactions between such processes if (ISO 9001: 2000). Its ultimate purpose is to ensure that all processes of an organization or an entity to develop a coordinated, improving effectiveness, and satisfaction of all stakeholders; (customers, employees, suppliers, society in general).